A Critical Appraisal of 25 Years of Research About Fashion Adoption Groups: Part 1. Theories/Models and Research Methods. (October 2017) - Workman, Jane E.; Lee, Seung-Hee
A critical appraisal of 52 articles about fashion adoption groups published from 1989 to 2013 was presented in this article. Objectives were to evaluate use of theories/models, demographics, research methods, and terms denoting fashion adoption groups. Information was compiled and organized to present a broad, updated, and more complete view of fashion adoption. Gaps and shortcomings were uncovered that provided ideas for future research. Detection of a variety of both theoretical and operational terminology and definitions provided a rationale for reaching consensus about terminology and definitions. Assessment of methods used to determine thresholds to segment consumers highlighted a need for consistency in analysis and reporting.